Pengaruh kemampuan berpikir kritis terhadap hasil belajar matematika - Siti Komariyah; Ahdinia Fatmala Nur Laili (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2018)
Mathematics is a very important lesson given to all learners, given the development of increasingly modern technology that is in dire need of human humans to have the ability to think critically, logically and systematically.Mathematics courses need to be given to all learners to equip learners with logical, analytical, systematic, critical, and creative thinking skills. This study was conducted in order to determine the effect of critical thinking ability on student learning outcomes in the subjects of mathematics class VIII SMP 1 Sumbergempol. The method used in this research is the quantitative method. The population used in this study is class VIII SMP 1 Sumbergempol, while the sample taken is a student class VIII C amounted to 20 students. The instrument used to obtain the data in this study is a matter of description test, which amounted to 2 questions. The technique of collecting data with observation, test, and documentation. Research results obtained t count value is greater than the value t table (t count = 5.173  ³  t table = 2.101), thus Ho is rejected and Ha accepted. It is evident that critical thinking has a significant effect on mathematics learning outcomes. From a result of data analysis obtained r value equal to 0,598. While the contribution of critical thinking to the result of learning mathematics is equal to 59,8% and the rest equal to 40,2% determined by other factors. The simple regression equation is: Y = 67,032 + 0,341X. The constant of 67,032 states that if the value of critical thinking is 0, then the ability to solve the student math problem is 67.032. The regression coefficient of 0.341 states that any addition of 1% value on critical thinking will improve the mathematics learning outcome of 0.341.